How does the spaceborne radar blind zone affect derived surface snowfall statistics in polar regions?. Issue 24 (16th December 2014) - Maahn, Maximilian; Burgard, Clara; Crewell, Susanne; Gorodetskaya, Irina V.; Kneifel, Stefan; Lhermitte, Stef; Van Tricht, Kristof; van Lipzig, Nicole P. M.
Abstract Global statistics of snowfall are currently only available from the CloudSat satellite. But CloudSat cannot provide observations of clouds and precipitation within the so‐called blind zone, which is caused by ground‐clutter contamination of the CloudSat radar and covers the last 1200 m above land/ice surface. In this study, the impact of the blind zone of CloudSat on derived snowfall statistics in polar regions is investigated by analyzing three 12 month data sets recorded by ground‐based Micro Rain Radar (MRR) at the Belgian Princess Elisabeth station in East Antarctica and at Ny‐Ålesund and Longyearbyen in Svalbard, Norway. MRR radar reflectivity profiles are investigated in respect to vertical variability in the frequency distribution, changes in the number of observed snow events, and impacts on total precipitation. Results show that the blind zone leads to reflectivity being underestimated by up to 1 dB, the number of events being altered by ±5% and the precipitation amount being underestimated by 9 to 11 percentage points. Besides investigating a blind zone of 1200 m, the impacts of a reduced blind zone of 600 m are also analyzed. This analysis will help in assessing future missions with a smaller blind zone. The reduced blind zone leads to improved representation of mean reflectivity but does not improve the bias in event numbers and precipitation amount.